2022
DOI: 10.3390/nano12071143
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Biopolyol-Based Waterborne Polyurethane Modified through Complexation with Chitosan

Abstract: In this study, a series of castor oil-based anionic waterborne polyurethane (CWPU) systems, which it has been suggested may be suitable for use as green elastomers with diverse applications in films and coatings, was prepared by modified with O-carboxymethyl chitosan (CS) as not only a reinforcing filler, but a chain-extender of polyurethane prepolymer to enhance the properties of polyurethanes. Moreover, not only was the system obtained with castor oil-based polyol in the absence of a catalyst, but it was mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The reason for the favorable mechanical properties of CWPUs is the addition of chitosan oligosaccharide improves the content of hard segments in polyurethane, resulting in the increase of stress and initial modulus. [ 40 ] In addition, COS causes a large number of chemical cross‐linking structures in polyurethane molecules (Figure 2i), which effectively limits the molecular chain slippage under tension. It means that more force is required to achieve the same strain.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the favorable mechanical properties of CWPUs is the addition of chitosan oligosaccharide improves the content of hard segments in polyurethane, resulting in the increase of stress and initial modulus. [ 40 ] In addition, COS causes a large number of chemical cross‐linking structures in polyurethane molecules (Figure 2i), which effectively limits the molecular chain slippage under tension. It means that more force is required to achieve the same strain.…”
Section: Resultsmentioning
confidence: 99%
“…Biocompatibility is not affected, as it is a surface property, while the mechanical properties are bulk properties. Choi et al synthesized nanocomposite polymers with waterborne polyurethane (WPU) and chitosan, and for the mechanical properties, they observed that the inclusion of chitosan increased their strength and elongation, and the authors attributed this to the hard and soft segments due to the addition of Ch as a chain extender because the Ch chains are stiffer and can affect the elasticity of the resultant films by cross-linking and hydrogen bonding with CWPU chains [ 26 ]. The inclusion of Ch, which is a stiffer molecule, as a filler in the matrix affects the mobility of the chain, which reduces the tensile strength and elongation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%